Evaluating the online platform of a blended-learning pharmacist continuing education degree program. Issue 1 (1st January 2016) - Wilbur, Kerry
Abstract : Background: Distance-based continuing education opportunities are increasingly embraced by health professionals worldwide. Methods: To evaluate the online component of a blended-learning degree program for pharmacists, we conducted a structured self-assessment and peer review using an instrument systematically devised according to Moore's principles of transactional distance. The web-based platform for 14 courses was reviewed by both local and external faculty, followed by shared reflection of individual and aggregate results. Results: Findings indicated a number of course elements for modification to enhance the structure, dialog, and autonomy of the student learning experience. Conclusion: Our process was an important exercise in quality assurance and is worthwhile for other health disciplines developing and delivering distance-based content to pursue.